Mobile devices and mobile internet data services: Implications for mobile banking - Malaquias, Rodrigo F.; Hwang, Yujong (Human Technology, 2025)
Mobile devices allow users to access applications anytime and anywhere. Through mobile devices, users can download and get access to banking services, using mobile banking applications. In order to perform banking activities, users need to trust in this service first, and this includes the quality of the Internet connection. Moreover, considering that mobile devices have different screen sizes, these differences may also affect the intention to use mobile banking. Therefore, the aim of this paper was to analyze the potential effect of the size of mobile devices and of the mobile Internet data services on trust in mobile banking. The quantitative analysis includes descriptive statistics, confirmatory factor analysis and structural equation modeling. The main results suggest that mobile Internet data services presented a positive effect on trust in mobile banking, but the type of mobile device has no significant effect on trust. The discussion of the results considers the possibility of strategic alliances between different sectors to improve the adoption of mobile banking in developing countries.